원도급자 측면에서의 저가하도급 판정기준의 문제점과 개선방안 - 김순영; 한충희; 백태룡; 김균태; 이준복; Kim, Soon-Young; Han, Choong-Hee; Baek, Tae-Ryong; Kim, Kyoon-Tai; Lee, Jun-Bok (한국건설관리학회 논문집, 10(6), 2009)
As the Fundamentals of Construction Business Act was revised in December 2004 and its implementing ordinances and enforcement regulations were adjusted in June 2005, the screening system of low price subcontracting has been an obligation to the public owners, having brought about arguments for and against since it enacted in 1983. The statutes for low price subcontracting have been reinforced from this year; for example, it underlines to submit to a project and builds an information network of subcontracting works. The system's original intention was that prevents shoddy and fraudulent constructions caused by low price subcontracting and precludes disturbances of fair trade by screening that whether it satisfies the conditions or not in advance. But, the criterion for the existing low price subcontracting has several issues having held up a true mirror to the real situation. It is arguable to discharge an important task with the primary purpose. This dissertation have researched the problem with a deposit of subcontract and the low price subcontracting basic rate are being used by the criteria for deciding whether it is a low price subcontracting or not, so showing the plan of reformation based on the findings, it wishes to contribute toward making the most of the system's essential intent. 1983년 제정되어 찬반논란이 계속되고 있었던 저가하도급심사제도는 2004년 12월 건설산업기본법이 개정되고, 2005년 6월 동법시행령과 시행규칙을 개정함으로써 공공발주자에게는 의부사항이 되었으며, 최근 개정된 법령에서는 하도급계획서 제출을 강화하고 하도급공사정보망을 구축하는 등 저가하도급에 대한 관리가 강화되었다. 이 제도의 당초 도입취지는 저가하도급 여부를 사전에 심사함으로써, 저가하도급으로 인한 부실시공을 방지하고, 공정거래질서의 교란을 방지하는 것이었다. 그러나, 현행 저가하도급 판정기준에는 몇가지 문제점이 있어 그 도입취지대로 역할을 수행하는데 한계가 많은 실정이다. 본 논문은 현행 저가하도급 여부를 판단하는 기준으로 사용되는 원도급계약단가와 금액, 하도급낙찰률, 그리고 저가하도급 판단기준율에 대한 문제점을 고찰하고 그 분석 검토결과를 바탕으로 하여 개선방안을 제시함으로써, 저가하도급심사제도의 당초 도입취지를 살리는 데 기여하고자 한다.